Early contributions to infants' mental rotation abilities. Issue 4 (15th November 2017) - Constantinescu, Mihaela; Moore, David S.; Johnson, Scott P.; Hines, Melissa
Abstract: Some cognitive abilities exhibit reliable gender differences, with females outperforming males in specific aspects of verbal ability, and males showing an advantage on certain spatial tasks. Among these cognitive gender differences, differences in mental rotation are the most robust, and appear to be present even in infants. A large body of animal research suggests that gonadal hormones, particularly testosterone, during early development could contribute to this gender difference in mental rotation. Also, substantial evidence supports an influence of socialization on mental rotation performance. The present study investigated the relationship of two types of factors, early postnatal testosterone exposure and parental attitudes about gender, to mental rotation performance in 61 healthy infants (29 males, 32 females). We measured salivary testosterone at two time points: 1–2.5 months of age and 5–6 months of age. Infants' mental rotation performance and parents' attitudes about gender were assessed at 5–6 months of age. As predicted, testosterone concentrations were significantly higher in boys than girls in early infancy ( d = 0.54), and boys performed significantly better than girls on mental rotation ( d = 0.64). A significant positive correlation between testosterone at age 1–2.5 months and mental rotation was found only in boys ( r = 0.50, p = .01). A significant negative correlation between parents' gender‐stereotypical attitudes and mental rotation performance was found only in girls ( r = −.57, p = .002). These findings suggest that the early postnatal testosterone surge (also known as "mini‐puberty") may have organizational influences on mental rotation performance in boys, and that parents may influence their daughters' mental rotation abilities beginning very early in life. Abstract : We investigated mental rotation performance in healthy infants and its relationship to two types of factors: early postnatal testosterone exposure and parental attitudes about gender. Our findings suggest that the early postnatal testosterone surge may have organizational influences on mental rotation performance in boys, and that parents' gender‐stereotypical attitudes may influence their daughters' mental rotation abilities beginning very early in life.